Sustainable practices in geotechnical engineering: Forging pathways for resilient infrastructure - Ali Akbar Firoozi; Ali Asghar Firoozi; Mohammad Reza Maghami (Results in Engineering)
This paper explores transformative advancements in sustainable geotechnical engineering through the integration of environmental stewardship, economic viability, and social equity into contemporary infrastructure practices. It synthesizes theoretical frameworks, innovative material applications, advanced soil stabilization techniques, and the incorporation of renewable energy systems to provide a comprehensive overview of sustainable strategies that enhance infrastructure resilience. Drawing upon global case studies, the study identifies critical success factors and recurring implementation challenges associated with sustainable geotechnical solutions. The findings indicate that the use of recycled and locally sourced materials, bioengineering methods for soil improvement, and renewable energy integration not only reduces environmental impacts but also enhances economic efficiency and extends infrastructure longevity. Furthermore, emerging materials such as volcanic ash composites and biopolymers exhibit considerable promise for future sustainable construction practices. The review underscores the pivotal role of policy initiatives and education in promoting sustainable geotechnical engineering and highlights the necessity of a multidisciplinary approach to achieve resilient, future-ready infrastructure systems.